The role of fetal magnetic resonance imaging. Issue 2 (10th February 2009) - Wright, C; Sibley, C P; Baker, P N
Abstract : The role of magnetic resonance imaging (MRI) in fetal imaging is expanding. The depth of structural information provided by MRI means it is more than just a useful adjunct to ultrasound, as several structures are more clearly visualised and many of the limitations of ultrasound are avoided. Currently, MRI is most frequently utilised with reference to the fetal central nervous system and is valuable in ventriculomegaly, agenesis of the corpus callosum and posterior fossa abnormalities. Outside this, MRI remains primarily a research tool; there is increasing interest in applying it to thoracic abnormalities and also scope for development in other niche areas. MRI is able to accurately determine fetal organ volumes and weight, although whether such measurements could play a role in conditions such as fetal growth restriction, has yet to be fully established. Techniques such as diffusion weighted imaging, magnetic resonance spectroscopy and functional imaging are also being remodelled for use in the fetus, improving our knowledge of in utero metabolism and development.